Spontaneous Resolution of Mirror Syndrome following Demise of Hydropic Twin - Kate E. Oliver; Kimberly W. Hickey; Scott M. Petersen (Hindawi Limited, 2012)
Maternal mirror syndrome is a rare consequence of fetal hydrops. By convention, delivery is recommended in pregnancies complicated by mirror syndrome due to grave fetal prognosis. We describe a case of a dichorionic, diamniotic twin gestation complicated by hydrops fetalis of twin B. The patient declined selective feticide. Two weeks later, intrauterine fetal demise of fetus B was diagnosed and complete resolution of mirror syndrome followed. Unaddressed, mirror syndrome can lead to significant maternal and fetal complications. This case illustrates resolution of mirror syndrome following spontaneous intrauterine demise of the hydropic fetus.